Management of High‐Risk Pregnancy 2007
DOI: 10.1002/9780470691878.ch5
|View full text |Cite
|
Sign up to set email alerts
|

Medications in Pregnancy and Lactation

Abstract: One of the least-developed areas of clinical pharmacology and drug research is the use of medication during pregnancy and lactation. This article is the first in a two-part series designed to familiarize physicians with many aspects of the drugs they commonly prescribe for pregnant and breast-feeding women. Almost every pregnant woman is exposed to some type of medication during pregnancy. Although the majority of pregnant and breast-feeding women consume clinically indicated or over-thecounter drug preparatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 224 publications
0
14
0
Order By: Relevance
“…Folic acid supplementation is recommended before conception and during pregnancy for mothers using certain antiepileptics (eg, carbamazepine) to decrease the risk of neural tube defects. 55 The lidocaine patch has not been studied in pregnancy; however, because its effect is local, systemic effects are presumed to be minimal. Nevertheless, this product should be used during pregnancy only if needed.…”
Section: Pharmacotherapy For Np During Pregnancy and Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…Folic acid supplementation is recommended before conception and during pregnancy for mothers using certain antiepileptics (eg, carbamazepine) to decrease the risk of neural tube defects. 55 The lidocaine patch has not been studied in pregnancy; however, because its effect is local, systemic effects are presumed to be minimal. Nevertheless, this product should be used during pregnancy only if needed.…”
Section: Pharmacotherapy For Np During Pregnancy and Breastfeedingmentioning
confidence: 99%
“…54 When pharmacotherapy is being considered during pregnancy and lactation, the crucial question is, Does the benefit of the drug outweigh its risks? 55 Experience with the use of drugs for NP during pregnancy is derived mainly from patients with epilepsy and severe depression. These conditions may be detrimental and even lifethreatening if untreated during pregnancy, which is not the case with NP.…”
Section: Pharmacotherapy For Np During Pregnancy and Breastfeedingmentioning
confidence: 99%
“…Even when the drug is no longer detectable in the body, the biochemical and physiological effects of drugs on the body may persist such that harm to the fetus is still possible. In utero exposure at different stages of pregnancy with the same drug can result in different outcomes [54]. Pregnancy loss occurs most commonly during the first 2 weeks after conception, whereas congenital anomaly and impaired brain or growth development often occur later in pregnancy [54].…”
Section: Potential Biological Mechanism(s)mentioning
confidence: 99%
“…Oral and dental structures are frequently the sites of adverse drug reactions (Seymour & Rudralingham, 2008). Almost every pregnant woman is exposed to some type of medication during pregnancy (Buhimschi & Weiner, 2009). It was also reported that drugs or physical agents can adversely affect the human teeth during their embryonic development and after their eruption into the oral cavity (Billings et al, 2004).…”
Section: Introductionmentioning
confidence: 99%